Insights into the Regional Transport and Local Formation of Secondary Organic Aerosol in Delhi, India - Himadri Sekhar Bhowmik; Sachchida Nand Tripathi; Ravi Sahu; Ashutosh Kumar Shukla; Vipul Lalchandani; Shamitaksha Talukdar; Nidhi Tripathi; Lokesh Sahu (Aerosol and Air Quality Research)
Abstract The organic carbon (OC) and elemental carbon (EC) content were measured from PM2.5 quartz filter substrates collected over 24 hours in Faridabad, a heavily polluted city in Delhi national capital region (NCR), during January–February 2018. In this study, the secondary fraction of OC (SOC) was calculated using the “EC-tracer method”, and subsequently, secondary organic aerosol (SOA) was calculated. Two typical episodes were observed where SOA was elevated for multiple days. These occurrences were investigated for aged SOA formation through multi-day regional transport and locally generated SOA using ozone (O3), carbon monoxide (CO), nitric oxide (NO), and volatile organic compounds (VOCs) as supplementary data. Higher OC/EC ratios during these episodes could be due to a strong primary source, and this possibility cannot be ruled out. However, similar sulfate dynamics with SOA consolidated the multi-day regional transport of SOA during the elevated SOA episodes. The moderate resolution imaging spectroradiometer (MODIS) fire count, planetary boundary layer height (PBLH) data, temperature, and RH were examined to strengthen the hypothesis that the elevated SOA days were due to multi-day regional transport of SOA and not locally formed. The ratios of volatile organic compounds (VOC) were analyzed to understand the origins of VOCs and also to explore the regional transformation and local formation of SOA. The toluene/benzene (T/B) and isoprene/benzene (I/B) ratios were observed during the multi-day elevated SOA episodes to distinguish the regional and local sources of VOCs. Concentration weighted trajectory (CWT) plots also confirmed our hypothesis. This study suggests that the higher SOC fraction during those episodes was most likely due to regional or aged SOA formation. Also, multi-day regional transport contributes to the higher and elevated SOA episodes during January–February 2018.